THE ROLE OF TOURISM IN THE WORLD, A COMPARISON OF ASIAN AND EUROPEAN TOURISM SERVICES AND AN EXAMINATION OF CERTAIN TOURISM PROBLEMS - Tukhliev Iskandar Suyunovich; Azamatova Nozima Jaxongirovna (Scholar Express Journal, 2023)
The most used types of tourism worldwide.Tourism in Europe and Asia Problems in the tourism service around the world
Keywords: Service of tourism; domestic industry; scenic spots; historical monuments